Walking-Relations: On The Walk by Robert Walser and All This Can Happen by Siobhan Davies and David Hinton - Maren Butte (The International Journal of Screendance, 2016)
The article explores figurations of movement in Siobhan Davies’ and David Hinton’s found footage film All This Can Happen (2012), which refers to the work of prose The Walk (Der Spaziergang, 1917) by Robert Walser. It focuses on walking as act from a perspective of movement analysis in performance and dance studies. The essay unfolds questions about the filmic rhythm and montage in relation to the bodily movement of walking and its discursive contexts. It analyzes figurations like rhythm and pace, balance and imbalance, (dis-)orientation, relations to space and to others (choreography, social dimensions). This article argues that Davis’s and Hinton’s mise en scène generates a specific mode of physically engaged, aesthetic experience for the viewer by blending in visual composition with sensations of bodily movement.
Keywords: walking as act; movement analysis; flâneur; choreography; relationality; performance studies; dance studies; (post-)modernity; rhythm; montage; bewegungsgestalt